EVALUATION ON THE EFFECTIVENESS OF INTERVENTIONS ON ENHANCING KNOWLEDGE AND PRACTICES REGARDING HAND, FOOT AND MOUTH DISEASE PREVENTION AMONG MOTHERS WITH CHILDREN UNDER FIVE YEARS OLD AT KINDERGARTENS IN LONG HO DISTRICT, VINH LONG PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Hand, foot and mouth disease (HFMD) is a common infectious illness in children under five years old and can develop into outbreaks if preventive measures are ineffective. Mothers’ correct knowledge and practices play a crucial role in disease control.Objectives: To determine the proportion of mothers with correct knowledge and practices regarding HFMD prevention, and to assess the effectiveness of an intervention in improving knowledge and practices among mothers with children under five years old in kindergartens in Long Ho District, Vinh Long Province, in 2025.Subjects and Methods: A pre–post intervention study was conducted on 400 mothers whose children are attending kindergartens in Long Ho District. Data were collected using a standardized questionnaire on HFMD-related knowledge and practices. The intervention's effectiveness was evaluated through active health education communication, using Chi–square analysis and the Effectiveness Index (EI), with statistical significance set at p
Keywords: HFMD, knowledge, practice, mothers with children under five years old, Vinh Long.